Niger's Infrastructure : A Continental Perspective - Domínguez-Torres, Carolina; Foster, Vivien (World Bank, Washington, DC, 2017)
Between 2000 and 2005 infrastructure made a net contribution of only 0.3 percentage points to the improved per capita growth performance of Niger, one of the lowest in Sub-Saharan Africa. Raising the country's infrastructure endowment to that of the region's middle-income countries (MICs) could boost annual growth by about 4.5 percentage points, mainly by improving the condition of the road network. Niger has made significant progress in some areas of its infrastructure. Important reforms liberalizing the water supply and information and communication technology (ICT) sectors have boosted performance. In particular, reforms in urban water are among the most promising on the continent. Increased competition in the ICT market has contributed to the rapid expansion of mobile services. NIGELEC, the national power utility, has enhanced its performance. The Nigerien portions of regional corridors are in relatively good or fair condition. Air transport connectivity has improved. Niger has the potential to close this funding gap by tapping alternate sources of financing or adopting lower-cost technologies. There is plenty of room for private sector participation in Niger's infrastructure sectors, in particular ICT. Meanwhile, the adoption of alternate lower-cost technologies in the water supply, power, and road sectors would reduce the financing gap by almost a half ($219 million).